Set f(x), the yvalue, equal to zero, and then solve for x.
f(x) = (x² + 2x  8)(x  6) (x² + 2x  8)(x  6) = 0 {set f(x) equal to zero} (x + 4)(x  2)(x  6) = 0 {factored x² + 2x  8 into two binomials} x + 4 = 0 or x  2 = 0 or x  6 = 0 {set each factor equal to zero} x = 4 or x = 2 or x = 6 {solved each equation for x} (2,0) , (6,0), and (4,0) are the zeros of the function. Ask Algebra House
0 Comments
Your comment will be posted after it is approved.
Leave a Reply. 
Latest Videos
Archives
May 2024
